When culture meets child rights: Confucian ethics and legal challenges in mental health protection for minors in China - Li, Taoying; Zheng, Long (Frontiers in Public Health, 2025)
Against the backdrop of growing global awareness of children’s rights protection, mental health issues among minors in China have gradually gained social attention. However, the current legal system faces significant tensions between institutional provisions and cultural adaptations, resulting in the poor enforcement of certain legal provisions and a failure to effectively address the psychological challenges faced by adolescents. This paper explores the dual impact of Confucian values on adolescents’ mental health: on one hand, its emphasis on respecting teachers, valuing education, diligence in learning, and adherence to etiquette helps maintain educational order; on the other hand, its hierarchical obedience and shame-oriented approach may suppress individual emotional expression and hinder psychological support behaviors. Based on an analysis of the root causes of the conflict between China’s current legal system and cultural norms, this paper adopts an interdisciplinary perspective, integrating developmental psychology, children’s rights law, and Confucian ethics to propose a “culturally adaptive mental health rights protection framework.” This framework aims to achieve effective protection of minors’ mental health while facilitating the modern transformation of traditional culture through a combination of legal empowerment and cultural change. This paper proposes a culturally adaptive framework for safeguarding minors’ mental health rights, clarifying how tensions between Confucian ethics and the Convention on the Rights of the Child (CRC) can be reconciled through layered approaches at both the institutional and practical levels. It aims to provide theoretical grounding and policy guidance for the localized construction of China’s child-rights protection mechanisms.